Perovskite Solar Cells and Light Emitting Diodes: Materials Chemistry, Device Physics and Relationship - Yuan, Ligang; Xue, Qifan; Wang, Feng; Li, Ning; Waterhouse, Geoffrey I.N.; Brabec, Christoph; Gao, Feng; Yan, Keyou (Chemical Reviews, 2025)
Solution-processed perovskite solar cells (PSCs) and perovskite light emitting diodes (PeLEDs) represent promising next-generation optoelectronic technologies. This Review summarizes recent advancements in the application of metal halide perovskite materials for PSC and PeLED devices to address the efficiency, stability and scalability issues. Emphasis is placed on material chemistry strategies used to control and engineer the composition, deposition process, interface and micro-nanostructure in solution-processed perovskite films, leading to high-quality crystalline thin films for optimal device performance. Furthermore, we retrospectively compare the device physics of PSCs and PeLEDs, their working principles and their energy loss mechanisms, examining the similarities and differences between the two types of devices. The reciprocity relationship suggests that a great PSC should also be a great PeLED, motivating the search for interconverting photoelectric bifunctional devices with maximum radiative recombination and negligible non-radiative recombination. Specific requirements of PSCs and PeLEDs in terms of bandgap, thickness, band alignment and charge transport to achieve this target are discussed in detail. Further challenges and issues are also illustrated, together with prospects for future development. Understanding these fundamentals, embracing recent breakthroughs and exploring future prospects pave the way toward the rational design and development of high-performance PSC and PeLED devices.
CRIS-Team Scopus Importer:2025-05-30